The Effectiveness of Group Counseling with Role-Playing Techniques to Increase Student Empathy - Nurhasanah Nurhasanah; Neviyarni S.; Z. Mawardi Effendi (Universitas Negeri Padang, 2019)
Empathy is an important ability that must be developed and developed in students representing youth, as human beings who experience a transition of empathy need students to be able to improve what other people think and think that might happen quarrels, fights, bullying, and other actions, the lives of students more calm and peaceful. Today there has been an erosion of empathy in students this is caused by dependence on gadgets, instrumental learning, competition, differences, depression, alcohol, and other. The purpose of this study is to increase students' empathy using group guidance with role playing techniques. This research is a quasi-experimental study using quantitative methods and the non-equivalent control group design. The subject of this study were students of class VIII MT S N 1 Payakumbuh. The research instrument used an empathy scale that met the requirements of the research instrument, then analyzed using the Faired sample t test and the independent sample t test. This research cannot be applied to everyone, it needs further development. The findings of this study indicate group guidance with effective play techniques to improve students. These findings will be discussed further.